Root volume and dry matter of peanut plants as a function of soil bulk density and soil water stress - Duruoha, Charles; Piffer, Cassio Roberto [UNESP]; Silva, Paulo Roberto Arbex [UNESP] (My University, 2008)
Soil compaction may be defined as the pressing of soil to make it denser. Soil compaction makes the soil denser, decreases permeability of gas and water exchange as well as alterations in thermal relations, and increases mechanical strength of the soil. Compacted soil can restrict normal root development. Simulations of the root restricting layers in a greenhouse are necessary to develop a mechanism to alleviate soil compaction problems in these soils. The selection of three distinct bulk densities based on the standard proctor test is also an important factor to determine which bulk density restricts the root layer. This experiment aimed to assess peanut (Arachis hypogea) root volume and root dry matter as a function of bulk density and water stress. Three levels of soil density (1.2, 1.4, and 1.6g cm-3), and two levels of the soil water content (70 and 90% of field capacity) were used. Treatments were arranged as completely randomized design, with four replications in a 3×2 factorial scheme. The result showed that peanut yield generally responded favorably to subsurface compaction in the presence of high mechanical impedance. This clearly indicates the ability of this root to penetrate the hardpan with less stress. Root volume was not affected by increase in soil bulk density and this mechanical impedance increased root volume when roots penetrated the barrier with less energy. Root growth below the compacted layer (hardpan), was impaired by the imposed barrier. This stress made it impossible for roots to grow well even in the presence of optimum soil water content. Generally soil water content of 70% field capacity (P<0.0001) enhanced greater root proliferation. Nonetheless, soil water content of 90% field capacity in some occasions proved better for root growth. Some of the discrepancies observed were that mechanical impedance is not a good indicator for measuring root growth restriction in greenhouse. Future research can be done using more levels of water to determine the lowest soil water level, which can inhibit plant growth.
Keywords: Root growth; Root volume; Soil bunk; Soil compaction; Water stress; Compaction; Greenhouses; Mechanical permeability; Plants (botany); Soils; Stresses; Water content; bulk density; compaction; dry matter; experimental study; legume; root; water content; water stress; Arachis hypogaea